Contemporary Aspects of European Transport Policy - Zajac, Grzegorz; University of Information Technology and Management in Rzeszow (Journal of International Trade, Logistics and Law, 2015)
The origin of the common transport policy was in 1957. Currently the Treaty on the Functioning of the European Union (TFEU) of 2007 signed in Lisbon is legally binding concerning the common transport policy of the EU. The dynamic pace of the implementation of the common transport policy the EU was commenced from the beginning of the 1990s’ of the last century. The recognition of the importance and the role of transport for the EU as a whole by the Member States has created opportunities for the development of this branch of the economy, which for almost thirty years of the European integration was being marginalized. In contemporary rules about the common transport policy most barriers to its functioning throughout the continent were eliminated. For the EU the Trans-European Transport Networks (TEN-T) importance stems also from the fact that it should contribute to the achievement of greater economic and spatial cohesion of the European Union. The task of the TEN-T network is to increase the technical standardization of individual national networks, improvement of transport infrastructures, access facilitation to infrastructure and fostering better connections between national networks and transport modes. Today we can say without hesitation, that there has been huge progress in the implementation of the common transport policy in the EU. Codification and harmonization of laws at EU level contributes to the development of specific sectors of transport and strengthens European identity in the world.